Metode Everyone Is A Teacher Here Pada Mata Pelajaran SKI Terhadap Hasil Belajar Siswa Kelas VIII di MTS Al Futuhiyah Bumen Bumirejo Mojotengah Wonosobo - Khamdan Nahi Asrofi; Sri Haryanto; Ali Imron (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to determine the influence of the Everyone is Teacher Here method on student learning outcomes in SKI subjects, to determine the improvement and difference in student learning outcomes that use the Everyone is Teacher Here method and those who do not use the Everyone is Teacher Here method in SKI subjects. This thesis research uses a quasi-experimental method with pretest posttest design in two classes. The experimental class uses the Everyone is Teacher Here method, while the control class uses conventional learning. The data was analyzed using the t-test and gain test to determine the difference and improvement of learning outcomes. The results of the study show that there is an influence of the everyone is a teacher here method on student learning outcomes. This is evidenced by the difference in student learning outcomes in SKI lessons that use the everyone is a teacher here method and those who use the conventional method with t-test results >good at a significance level of 1%, which is 4.32 > 2.677. Meanwhile, at the level of 5% significance, it is 4.32 > 2.008. There is an increase in student learning outcomes after using the everyone is a teacher here method. This is evidenced by the results of the gain test for the experimental class obtained a result of 0.538.